Civic Education Learning Evaluation Model Aligned with the Merdeka Curriculum - Rani; Moh Restu Hoeruman (Journal of Contemporary Islamic Primary Education, 2025)
This research aims to develop an evaluation model for Civic Education learning that aligns with the principles of the Merdeka Curriculum (Freedom Curriculum). The research employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) conducted in five secondary schools in Central Java Province over a six-month period, involving 15 Civic Education teachers and 230 students. The findings indicate that the project-based and portfolio-based Civic Education evaluation model with integrated continuous formative assessment can enhance students' critical thinking abilities by 34.7% and citizenship skills by 29.3% compared to conventional evaluation models. The developed evaluation model received high validation scores (4.75 out of 5) from curriculum and Civic Education learning experts, as well as good practicality ratings (4.25 out of 5) based on teacher assessments.